Penguatan Identitas Kewargaan Melalui Pendidikan Multikultural Berbasis Kearifan Lokal: (Studi Kasus di Kabupaten Gorontalo) - Faradiba Azzahra; Roni Lukum; Fidya Ramadhani Abdullah Dede; Nurinda Ibrahim; Eka Haspy Mulbiyanti (JURNAL RISET RUMPUN ILMU PENDIDIKAN, 2026)
This article discusses strengthening civic identity through multicultural education based on local wisdom in Gorontalo Regency. The main problem raised is how local culture, although recognized as a symbol of regional identity, has not been fully translated into an inclusive and reflective pedagogical design to shape students' civic awareness. This study uses a qualitative case study design based on document analysis, with data sources in the form of indexed journal articles, regional official publications, and educational documents published in 2021–2026. The focus of the study is directed at educational practices in Limboto and Dungaliyo. The data was selected purposively based on relevance, credibility, and thematic proximity, then analyzed through the stages of data reduction, data presentation, and conclusion drawn. The results of the study show three main findings: first, huyula local wisdom as the value of mutual cooperation, solidarity, and collective responsibility functions as a cultural bridge that connects social diversity with civic disposition. Second, multicultural education is more effective when local values are explicitly integrated into classroom interactions, school habituation, collaborative work, and reflective discussions. Third, challenges arise because many local values are still implicitly practiced so that they have not yet formed a reflective citizenship consciousness. This article concludes the need for a shift from symbolic recognition to structured pedagogical design through curriculum contextualization, teacher mediation, and school-to-community partnerships.